Financial Performance: Islamic Corporate Governance, Islamic Corporate Social Responsibility, and Intellectual Capital - Nasiradi Al Jailani, Tohadi Luqman; Abdani, Fadlil (Universitas Gorontalo, 2025)
This study aims to examine the impact of Islamic Corporate Social Responsibility (ICSR), Islamic Corporate Governance (ICG), and Intellectual Capital (IC) on the financial performance of Islamic banks in Indonesia and Malaysia. Ten Islamic commercial banks from Indonesia and Malaysia were selected as samples, with a five-year observation period. Quantitative descriptive analysis using Eviews 12 software was utilized to analyze the data. The results of the first hypothesis indicate that ICSR has a positive but insignificant effect on the financial performance of Islamic banks. The second hypothesis shows that ICG has a positive impact on the financial performance of Islamic banks. The third hypothesis reveals that IC has a positive and significant effect on the financial performance of Islamic banks.